Dietary glycerol monolaurate supplementation for the modification of functional properties of egg white protein. (27th February 2019) - Zhao, Minjie; Cai, Haiying; Liu, Mengyun; Deng, Lingli; Li, Yang; Zhang, Hui; Feng, Fengqin
Abstract: BACKGROUND: Understanding the interactions between feed additives and the functional properties of egg white protein (EWP) may offer novel insights into the effects of feed additives on laying hens and may provide an alternative for modification of the functional properties of EWP by using laying hens as bioreactors. Glycerol monolaurate (GML) is widely used in the food industry as an effective antibacterial emulsifier. In this work, the effects of three doses of dietary GML supplementation (150, 300, and 450 mg kg −1 hen) on the functional properties of EWP were investigated. RESULTS: The hardness of EWP gels was significantly improved by 300 and 450 mg kg −1 GML supplementation. Foaming capacity (FC) and foaming stability (FS) were increased after GML treatment; 450 mg kg −1 GML supplementation showed the most significant improvements, with 44.82% in FC and 23.39% in FS. Stabilization of EWP‐oil emulsions was also improved, supported by a slowed creaming process and the formation of smaller oil droplets. The heat denaturation temperature and rheological properties were also modified by dietary GML supplementation, implying improved thermal stability. CONCLUSION: Our study demonstrated that GML supplementation has the potential to modify the functional properties of EWP, broadening the application of GML and providing a new perspective for evaluation of the efficacy of feed additives. © 2019 Society of Chemical Industry